Shea detoxifies - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Biologists from the research French institutes IRD and INRA have found a new strain of the bacterium Escherichia coli in shea cake (see page 6).Normally found only in the stomach of warm-blooded animals, it can be used to transform toxins such as...